Respuesta :

Answer:

A

Step-by-step explanation:

That’s vertex form y=(x-k)^2+b, k being the x of the vertex, and b being the y, so just remember that formula. Since 3 is positive in the equation, it means the x value of the vertex is -3 (since in the formula it is -k and a negative times a negative is a positive, if that makes any sense) and the y value of the vertex is -2, so the vertex of this equation is (-3,-2) which is the same on the graph!

Answer:

A. y = 2(x+3)² - 2

Step-by-step explanation:

2(x+3)² - 2 = 0

(x+3)² = 1

x+3 = ± 1

x = -2 or x = -4